Fikih dan pembangunan karakter: Membentuk individu dan masyarakat yang bermoral - Syahputra, Muhammad Akmal (Maliki Interdisciplinary Journal, 2024)
The role of jurisprudence in building moral individual character and society is as a legal science that provides solid moral and ethical guidance. In character education, fiqh has an important role in helping individuals and society in forming character in accordance with the guidance of Allah SWT and the norms that apply in society. By understanding Allah SWT’s guidance relating to faith, piety, honesty, justice and courage, individuals and society can form moral behavior and in accordance with Allah SWT’s guidance. Fiqh also helps individuals and society in forming the personal abilities needed in character education, such as the ability to develop positively, the ability to develop democratically, and the ability to develop at times. With good character education, society can form individuals who are moral and have noble character, who can help build a harmonious and ethical society. In the turbulent modern era, the role of jurisprudence in building moral individual character and society has become increasingly important. With comprehensive Islamic knowledge, fiqh has an important role in forming individuals with morals and noble character, who can help build a harmonious and understanding society